LEIOMYOMA OF THE ANTERIOR ABDOMINAL WALL IN A 26 YEAR OLD PREGNANT WOMAN: A CASE REPORT - Qamar, Saima; Mustafa, Nilofar; Khalil, Adeeba Akhtar; Jamil, Muhammad (Pakistan Armed Forces Medical Journal, 2020)
A uterine fibroid, also known as uterine leiomyoma is a benign smooth muscle tumor of the uterus. Although intramural fibroids located within the wall of the uterus are the most common type of uterine leiomyomas, fibroids can also be found in supporting structures such as the broad ligament. The incidence among women is generally 20-25 %. Abdominal wall fibroids, however, are an uncommon finding and are thought to be due to seeding following surgical resection of uterine fibroids.